EXTERNAL FACTORS OF ECONOMIC DEVELOPMENT OF THE EUROPEAN UNION - Akbarova , Mohinur Farxod qizi (GOLDEN BRAIN, 2024)
The economic development of the European Union is influenced by a myriad of external factors that play a crucial role in shaping its growth trajectory. These external factors include global economic trends, political stability, international trade agreements, technological advancements, and environmental sustainability, among others. Understanding how these external factors impact the EU’s economic development is essential for policymakers, economists, and stakeholders to formulate effective strategies and policies that promote sustainable growth and prosperity. This research aims to analyze the interplay between external factors and the EU’s economic development, shedding light on the importance of international cooperation, innovation, and regulatory frameworks in fostering economic resilience and competitiveness in an increasingly interconnected and dynamic global economy. By examining the complex relationships between external factors and economic development, this study seeks to provide valuable insights into the challenges and opportunities facing the EU in the 21st century.